2013
DOI: 10.7897/2230-8407.04715
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Nanosilver as a Potential Antibacterial and Antifungal Additive to Commercially Available Dish Wash and Hand Wash for an Enhanced Antibacterial and Antifungal Activity Against Selected Pathogenic Strains

Abstract: In the present study, biogenic silver nanoparticles rapidly synthesized using leaf extract of Rosa indica -wichuriana hybrid Francois guillot were investigated for their potential use as a antibacterial and antifungal additive to commercially available dish wash and hand wash. UV-vis spectrophotometer, Powder X-ray diffraction, FTIR spectroscopy, HrTEM and EDX analysis were used to characterize the synthesized silver nanoparticles. UV-vis spectrum analysis showed the surface plasmon peak at 427 nm. From high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The band detected at 2857.99 cm −1 was described [32] as C–H stretching corresponding to aromatic mode arises from aromatic amino acids. Other distinct peaks were recorded 2362.37, 1423.21 and 1238.08 cm −1 corresponding to –COO [33], –CH 3 bending bonds [34] and C–C stretching vibration of alkanes [26], respectively. In addition, the weak peak with a wavelength 765.60 cm −1 was suggested as –CH by [35].…”
Section: Resultsmentioning
confidence: 99%
“…The band detected at 2857.99 cm −1 was described [32] as C–H stretching corresponding to aromatic mode arises from aromatic amino acids. Other distinct peaks were recorded 2362.37, 1423.21 and 1238.08 cm −1 corresponding to –COO [33], –CH 3 bending bonds [34] and C–C stretching vibration of alkanes [26], respectively. In addition, the weak peak with a wavelength 765.60 cm −1 was suggested as –CH by [35].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, many species have been reported to be resistant to many commonly used antifungal agents. According to Rajarathinam and Kalaichelvan, AgNPs can be the appropriate agents for the control of three Candida species, namely, C. albicans , C. tropicalis , and C. krusei . Further, they also demonstrated its application as additive in commercially available dish and hand wash. Another study by Monteiro et al has also proved the potential of AgNPs against C. albicans and C. glabrata .…”
Section: Therapeutical Uses Of Agnpsmentioning
confidence: 99%
“…; Hwang et al . ; Rajarathinam and Kalaichelvan ). However, only few studies have been performed to assess the effects of AgNPs on dermatophytes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported potent antifungal activity of AgNPs against pathogenic fungi, and most of them have been focused on the effect of AgNPs on the Candida species (Chwalibog et al 2010;Monteiro et al 2011;Nasrollahi et al 2011;Hwang et al 2012;Rajarathinam and Kalaichelvan 2013). However, only few studies have been performed to assess the effects of AgNPs on dermatophytes.…”
Section: Introductionmentioning
confidence: 99%